Mindful parenting—A thematic exploration of narratives from Indian mothers - Mazumdar, Ketoki; Parekh, Sneha; Sen, Isha (Frontiers in Global Women's Health, 2023)
With the global crisis of the COVID-19 pandemic continuing, Indian mothers have not received adequate attention with respect to their challenges and mothering experiences. The current study explored mindful parenting practises in a cohort of Indian mothers of children aged 10 years and below, that emerged in response to the challenges posed by COVID-19. In-depth virtual interviews were conducted with 31 urban Indian mothers. The data were thematically analysed. The study identified two overarching themes and eight sub-themes. The first theme Pandemic induced stress includes the sub-themes of increased workload, poor support system, lack of time for self and emotional and physical distress. The second theme of Mindful Parenting includes awareness of self and child, acceptance of self and child, empathic understanding of self and child and active engagement with child. Increased workload on all fronts coupled with poor support and lack of time for self contributed to exacerbated emotional and physical stress in mothers. They addressed these concerns by engaging in Mindful parenting processes in their mothering practises. Mindfulness-based Cognitive Therapy, Mindfulness based Stress Reduction and Mindfulness based parenting techniques could be explored as possible interventions for mothers to alleviate their distress. Keywords: Indian Mother, COVID-19, Mindful Parenting, Parenting stress, Qualitative research.